Challenges in regulating priority setting in healthcare: A Finnish perspective on the lawmaker's dilemma. (June 2019) - Kimmel, Kaisa-Maria
Healthcare rationing presents multiple problems for the lawmaker. This article examines them through two legislative projects concerning Finnish healthcare and the scope of professional discretion awarded to physicians in priority setting. In attempting to enact norms to steer decision-making in priority setting, the lawmaker has to balance tensions between individual and community rights; for example, relating to legal safeguards, equal access, clinical autonomy, individual need, and transparency. Physicians exercise significant discretion over rationing in a context of rising pressure to contain costs, without support from precise decision-making criteria set in legislation. This raises concerns over the long-term legitimacy of priority setting in Finland. The article argues that legal research should provide analyses of legislative measures and the wider regulatory mix to ensure that priority setting frameworks are compatible with the right to health, and that best practices presented in international priority setting research are operationalized in legislative reforms.